Research in fisheries science in selected Philippine universities an abstract bibliography, 1974-1995 - Gonzalez, Erlinda B. (1996)
This study was undertaken to identify the research areas chosen by graduate students as the subject of their theses of dissertations in four selected universities namely; Central Luzon State University (CLSU), the University of the Philippines Diliman, Marine Science Institute and the Department of Meteorology and Oceanography (UP), the University of the Philippines in the Visayas (UPV), College of Fisheries, and the University of San Carlos (USC) in Cebu City for the following master's degrees: M.Sc. Aquaculture, M.Sc. Fisheries (Aquaculture), M.Sc. Fisheries (Fish Processing Technology), M.Sc. Fisheries Biology, M.Sc. Marine Biology and M.Sc. Oceanography. The period 1974-1995 was chosen, 1974 being the year when the first master's degree in fisheries was instituted at the University of the Philippines. A Total of 342 theses and 2 dissertations were identified and analyzed. It was also aimed at finding out if the research areas meet the national research priorities identified by their respective agencies, at the same time to produce an abstract bibliography of these theses and dissertations that will minimize or solve the problem of bibliographic control of unpublished theses and dissertations in fisheries-related subjects.